Magneto transport on the surface of a topological insulator spin valve - Bumned Soodchomshom (2018)
The effects of the magnetization on the transport properties of a ferromagnet/barrier/ferromagnet spin valve fabricated with a topological insulator are studied. We consider two types of junctions, (i) an F1 / normal barrier (NB) / F2 junction and (ii) an F1 / magnetic barrier (FB) / F2 junction. The junctions in both cases lie in the xy-plane with the magnetizations in both ferromagnetic regions, F1 and F2 aligned in the z-direction. The charge carriers in the topological insulator have a Dirac like energy spectrum of a massive relativistic particle with the magnetization M playing the role of the mass. The gap opening is a special magneto feature of topological insulators. In an anti parallel alignment of the two magnetizations, the mass of the carriers is negative in the region where M is in the negative direction. The negative mass leads the behaviors of the magneto transport properties and the tunneling magneto resistance of these junctions to be quite different from those of graphene-based spin values. © 2010 Elsevier B.V. All rights reserved.